Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Bentuk Aljabar Kelas VII SMP - Pujisari, Anisa; , Rita Pramujiyanti Khotimah,S.Si, M.Sc (2016)
The purpose of research to describe the conceptual and procedural errors of students in solving the algebra class VII and analyze the factors causing the students to make mistakes. This type of research is qualitative descriptive. The subjects were students of class VII F SMP Negeri 3 Kartasura. Data collection methods are test, interviews, and documentation. Data analysis technique used is data reduction, data display, and conclusion. The results showed that students make mistakes in algebra solving. First, error conceptually divided into two, namely: (1) error in understanding the meaning of a material; (2) errors in understanding the basic concepts of algebra. Second, procedural errors are divided into two, namely: (1) error in the completion of the steps associated with the material prerequisites that must be understood; (2) errors in calculating an operation. Factors that cause the students make mistakes that student comprehension ability is low, less work practice questions are similar, yet able to translate material, too hasty in doing so is not rigorous in solving these problems and the weak of memory of students. Keywords: algebra, conceptual, error, procedural.